140 INSULIN RECEPTOR SUBSTRATE 2: A POSSIBLE MOLECULAR MARKER FOR RHABDOMYOSARCOMA TUMOR PROGRESSION. (1st January 2006) - Tang, R.; Davicioni, E.; Triche, TJ
Abstract : Rhabdomyosarcoma (RMS) is the most common soft tissue sarcoma of childhood associated with a skeletal muscle differentiation phenotype. Gene-expression profiles of 163 primary RMS tumors were identified and a prognostic "MetaGene" (a subset of 48 genes) was identified that can assign patients to low-, intermediate-, and high-risk groups. In particular, the expression profiles of high-risk patients were characterized by low expression of myogenic differentiation genes such as myogenin and high expression of mitogen-activated signal transduction pathway members that included insulin receptor substrate 2 (IRS2). IRS2 is known to regulate cell proliferation and survival and is known to be regulated in a serum-dependent manner in normal muscle cells. In this study, we measured IRS2 and myogenin mRNA levels in JR/C, a cell line model for highly aggressive alveolar RMS. JR/C cells were cultured under different serum conditions for RNA isolation and preparation of cDNA. Quantitative RT-PCR (QRT-PCR) was used to assess IRS2 and myogenin mRNA levels and found that myogenin mRNA increased in a serum-dependent manner. This is in contrast to normal muscle cells where myogenin mRNA is known to increase under conditions of decreased serum. IRS2 expression did not change and appears to be regulated in a serum-independent manner. These findings suggest that JR/C rhabdomyosarcoma cells exhibit a differentiation block and do not respond to changes in serum levels, as do normal muscle cells. In addition, IRS2 may be a crucial mediator of this block and associated with poorly differentiated tumors and poor patient outcome in high-risk RMS patients.